Medidas precautorias en el Arbitraje Internacional - Murillo González, Miguel Angel (UNIVERSIDAD DE SONORA, 2019)
Precautionary measures are an instrument of Justice that helps apply according to the law the full and effective implementation of a judgment or an arbitral award. The old debate about the scheme of distribution of competence between referees and judges about opposite acts to the arbitration agreement, it is exceeded as a result of the fulfillment, of an arbitration agreement, litigation covering this already will be unresolved by the official courts of any State but by an arbitral tribunal. Thus the parties, by their own volition, exclude jurisdiction.